POLEX-SOUTH DATA, PART 4 : MICROMETEOROLOGICAL DATA AT MIZUHO STATION, ANTARCTICA IN 1980 - OHATA, Tetsuo; ISHIKAWA, Nobuyoshi; KOBAYASHI, Shun'ichi; KAWAGUCHI, Sadao (National Institute of Polar Research, 1983)
P(論文) departmental bulletin paper